Connected at school. Smartphone and Internet use among adolescents - Marco D'Agostini; Damiano Cantone; Stefania Pascut; Francesca Zanon; Susanna Feruglio (Firenze University Press, 2024)
This study, conducted on over 1800 students from second level secondary schools in the province of Udine, is the result of a survey on the use of smartphones in schools. The analysis is inspired by a questionnaire divided into three parts filled out anonymously by students on three main aspects: times and methods of smartphone use at school, pathological use of Internet, psychological well-being. The responses highlighted a series of elements that allow to open a critical reflection on the challenges that new technologies and in particular portable digital systems (smartphones) impose on the school system.   Connessi a scuola. L'uso dello smartphone e di Internet tra gli adolescenti. Questo studio, condotto su oltre 1800 studenti/esse delle scuole secondarie di secondo grado della provincia di Udine, è il risultato di un'indagine sull'utilizzo dello smartphone in ambito scolastico. L'analisi prende spunto da un questionario diviso in tre parti compilato anonimamente da studentesse e studenti su tre aspetti principali: tempi e modalità di utilizzo dello smartphone a scuola, uso patologico di Internet, benessere psicologico. Le risposte hanno messo in luce una serie di elementi che consentono di aprire una riflessione critica sulle sfide che le nuove tecnologie e in particolare i sistemi digitali portatili (smartphone) impongono al sistema scolastico.